Assessment of mother's ability in caries diagnosis, utilizing the smartphone photographic method - Sonal Kale; Pradnya Kakodkar; Sahana Hegde Shetiya (Wolters Kluwer Medknow Publications, 2019)
Background: Smartphone is proved to be reliable in teledentistry model. The aim of the study was to assess the mother's ability in caries diagnosis, utilizing the smartphone-based photographic method. Hypothesis: Mothers have the ability for caries diagnosis utilizing the smartphone photographic method. Methods: A cohort of 100 mothers was given health education regarding dental caries diagnosis. Then, their children from the preschools were screened by the dentist for dental caries using visual examination, followed by clicking intraoral photographs using Motorola 3G phone. The photographs were sent through WhatsApp to respective mothers, and they were asked to diagnose their child's dental status. Accuracy and reliability measures of mother's diagnosis were estimated by calculating the sensitivity, specificity, predictive values, and kappa value. Results: The calculated value for sensitivity was 88.3%, specificity was 98.3%, positive predictive value was 92%, negative predictive value was 97%, and accuracy was 96%. There was a strong agreement between mother's and dentist's diagnosis (kappa value of 0.87). Conclusion: Following the dental health education, it can be concluded that mothers are in a better position to diagnose their child's dental status through smartphone-based photographs.